Review of the state of the art between sustainability and hydropower generation: A vision from Asia - Sebastian Naranjo-Silva; Jorge Silva; Javier Alvarez-del-Castillo (Tecnología y ciencias del agua)
Hydroelectric energy is a widely used technology in 180 countries benefiting in 2020, this source has 140 years of development, represents 16 % of the energy generated in the world and 63 % of renewables. The objective of this manuscript is to develop a state of knowledge that analyzes scientific theories, hypotheses and projects to propose this review as a robust theoretical framework to understand the effects and advantages of hydroelectric energy in Asia. For the review, the methodology collected scientific information from publishers such as Elsevier, Taylor & Francis and Springer. The Asian continent was selected due to the representative number of hydroelectric projects, and to represent more than 30 % of the world's hydroelectric generation, having the largest installed capacity. According to studies in 13 Asian countries ―over future projections―, hydropower potential decreases over time in part due to the deep interaction between water and its location, variations in climate change and opposition from people near the sources and projects in often remote areas. The prominence of hydroelectricity will gradually change from a stable generation as a complementary source of other renewable energies. On the other hand, hydroelectricity, as the largest renewable source today, is competitive in generation price and responds to the growing demand of the population, therefore, to build sustainable energy systems, policymakers, engineers and builders must adopt procedures that organize projects based on sustainability criteria.